2021
DOI: 10.1007/s12144-021-02366-3
|View full text |Cite
|
Sign up to set email alerts
|

The benefits of beauty – Individual differences in the pro-attractiveness bias in social decision making

Abstract: While there already is a huge body of research examining the advantages and disadvantages of physical attractiveness in social and economic decisions, little research has been made to explore the role of individual differences in social decision-making with regard to beauty. To close this scientific gap, we conducted a multiparadigm online study (N = 210; 52% females) in which participants were asked to make decisions in four different economic games facing differently attractive counterparts. Additionally, th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
8
2

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 12 publications
(10 citation statements)
references
References 64 publications
0
8
2
Order By: Relevance
“…Saad & Gill, 2001) as well as both simultaneously (e.g. Croson & Gneezy, 2009;Voit et al, 2021). Moreover, there is evidence for gender differences in framing effects on allocation tasks (Chowdhury et al, 2017).…”
Section: Participantsmentioning
confidence: 93%
“…Saad & Gill, 2001) as well as both simultaneously (e.g. Croson & Gneezy, 2009;Voit et al, 2021). Moreover, there is evidence for gender differences in framing effects on allocation tasks (Chowdhury et al, 2017).…”
Section: Participantsmentioning
confidence: 93%
“…Additionally, a common trait in people with high agreeableness is the ability to empathise, and further evidence shows that people who are less empathetic tend to make riskier choices than those who are more empathetic (Uijong et al, 2019). Also, other research has found that high agreeableness as a trait is related to being more altruistic, trusting, and cooperative and in that regard high agreeableness would lead to less risky decision‐making (Voit et al, 2021).…”
Section: Agreeableness and Risky Decision‐makingmentioning
confidence: 99%
“…The core idea of deep residual learning is to introduce residual connections (also known as skip connections). As deep residual networks, such learning system can be abbreviated as ResNet [46][47][48][49][50][51] We chose ResNet-50 as the backbone of our learning system and will compare its performance with ResNet-18 and ResNeXt-50 at the end of Section 3. That is, the first residual block consists of three residual units, each of which consists of three convolutional layers.…”
Section: Deep Residual Learningmentioning
confidence: 99%